Serosurvey of Schmallenberg Virus Infection in the Highest Goat‐Specialized Region of France. Issue 5 (27th January 2014) - Valas, S.; Baudry, C.; Ehrhardt, N.; LeVen, A.; Thirion, M.; Aubert, C.; Vialard, J.
Summary The monitoring of both the spread and clinical impact of Schmallenberg virus (SBV) infection within its full host range is important for the control of the epidemic and potential new outbreaks. In France, a national surveillance plan based on voluntary notifications of congenital malformations in newborn ruminants revealed that goats were the less affected host species. However, seroprevalence studies only targeted sheep and cattle, preventing accurate estimations of the real impact of SBV infection in goats. Here, a serological survey was conducted in the highest goat‐specialized region of France between June 2012 and January 2013. A total of 1490 goat sera from 50 herds were analysed by ELISA. The between‐herd and within‐herd prevalences were estimated at 62% and 13.1%, respectively. Seroprevalence was not uniformly distributed throughout the territory and markedly differed between intensive and extensive herds. The low within‐herd seroprevalence demonstrates that a large fraction of the French goat population remains susceptible to SBV infection.